A new dynamic torque calibration device at PTB. (December 2021) - Klaus, Leonard; Kobusch, Michael
Abstract: Research in the field of dynamic torque calibration has gained some momentum in the last few years. At PTB, a calibration device for small dynamic torque levels up to about 0.5 N m proved the working principle of dynamic torque calibrations with sinusoidal excitation. In a next step, a new calibration device was developed with the intention of generating higher dynamic torque levels in the range of up to 20 N m. Although this is still less than many industrial applications require, it could pave the way to higher torque levels. The new calibration device features a horizontal arrangement of all components of the drive shaft. The device consists mostly of industrial components that have been modified, rather than custom-made components. After commissioning, optimising the device enabled a frequency range from 10 Hz to up to 400 Hz.